2021
DOI: 10.3390/su13052425
|View full text |Cite
|
Sign up to set email alerts
|

Towards Territorially Embedded, Equitable and Resilient Food Systems? Insights from Grassroots Responses to COVID-19 in Italy and the City Region of Rome

Abstract: The negative impacts of the COVID-19 pandemic have further exposed and exacerbated the structural weaknesses and inequalities embedded in the global industrial agri-food system. While the mainstream narrative continues to emphasise the importance of ensuring the uninterrupted functioning of global supply chains to counter COVID-related disruptions, the pandemic has also highlighted the resilience of small-scale, sustainable family farming and of spatially and socially embedded food systems. Based on a quantita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
33
0
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(39 citation statements)
references
References 61 publications
2
33
0
4
Order By: Relevance
“…Although the survey and interviews indicated that producers could adapt to Covid-19 related challenges, some respondents pointed out that provincial regulations followed a “watering can” approach (e.g., posing the same measures for sales at outdoor farms as for supermarkets). This somewhat mirrors initial findings, such as by Zollet et al (2021) , who identify concerns about preferential treatment of big players in Italy. Not only does this show insufficient agricultural emergency and insurance programs that were not designed for pandemics ( Ker, 2020 ) but also the lack of nuanced regulations for different types of operations.…”
Section: Resultssupporting
confidence: 83%
See 2 more Smart Citations
“…Although the survey and interviews indicated that producers could adapt to Covid-19 related challenges, some respondents pointed out that provincial regulations followed a “watering can” approach (e.g., posing the same measures for sales at outdoor farms as for supermarkets). This somewhat mirrors initial findings, such as by Zollet et al (2021) , who identify concerns about preferential treatment of big players in Italy. Not only does this show insufficient agricultural emergency and insurance programs that were not designed for pandemics ( Ker, 2020 ) but also the lack of nuanced regulations for different types of operations.…”
Section: Resultssupporting
confidence: 83%
“…It is not clear, however, whether consumer demand alone will or can drive local food systems and where Québec will hit physical, social, economic, and political boundaries. According to O'Hara and Low (2016) , local food sales are more tied to income fluctuations compared to non-local products, raising questions about willingness or ability to spend money on local food if economic concerns arise in the wake of Covid-19 ( Zollet et al, 2021 ). Hence, to what degree financial commitments, as found in CSA, or household income will determine continued support of local farmers has yet to be seen.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…At the same time, locally led initiatives have emerged in response to urgent and pressing food access challenges at the community scale [5,6]. Local and global policy arenas are not substitutes, but rather interconnected complements and powerful tools for reform.…”
Section: Introductionmentioning
confidence: 99%
“…In response to these impacts, actions have been taken by groups or individuals in society or governments to prevent, compensate for, or adapt to emerging changes. There are hints that local food actors have responded to the consequences and impacts by developing immediate decentralized collective strategies, and by implementing alternative practices under the umbrella of agroecology (Tittonell et al, 2021;Zollet et al, 2021). However, the particular changing conditions under which such practices have been implemented and what potentials they unfold within local food systems' sustainability transitions in time and in relation to the principles of agroecology (Wezel et al, 2020) remain to be further explored.…”
Section: Introductionmentioning
confidence: 99%